Mataano Mambio: Ritual and symbolism of the laporo tribe's harvest - Puspita Rizki, Dian; Asrani, Asrani (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study investigates the Mataano Mambio harvest ritual practiced by the Laporo ethnic community in Kombeli Subdistrict, Buton Regency, focusing on its ritual structure, symbolic meanings, and cultural significance. The research adopts a qualitative descriptive design, employing in-depth interviews, participant observation, and documentation conducted between January and March 2024. A total of 12 informants were selected using snowball sampling. Data were analyzed using Miles and Huberman’s interactive model, involving data reduction, data display, and conclusion drawing. Findings reveal that Mataano Mambio unfolds through a structured series of ritual events: beginning with Piharoaano Galampa (customary deliberation), followed by Bata Nda’a and Linda dances, Sungkuano Sadakaa (ritual prayer), Sumbele’a Bembe (goat sacrifice), the central Mataano Mambio ceremony, and concluding with Manca and Panguncei performances. Each element embodies symbolic meanings rooted in Laporo cosmology—such as humility, interdependence, ancestral reverence, and ethical trade. Interpreted through the lenses of cultural resilience theory, symbolic anthropology, and glocalization, the ritual functions as a living system of knowledge transmission and socio-ecological adaptation. The study contributes to cultural studies by demonstrating how indigenous rituals operate not only as cultural heritage but also as dynamic frameworks for sustaining identity, resilience, and collective memory amid social change.